1997
DOI: 10.1080/12538078.1997.10515779
|View full text |Cite
|
Sign up to set email alerts
|

Lutte contre les insectes phytophages par les plantes aromatiques et leurs molécules allélochimiques

Abstract: Resume.-Des observations ethnobotaniques ont montre qu'il existe dans le sud-ouest de Ia France une pratique traditionnelle de protection des graines de legumineuses par les plantes odorantes. L'efficacite de cette methode a ete evaluee en laboratoire. L'activite insecticide des plantes aromatiques s'exerce a deux niveaux : un eifel lethal sur les populations adultes et une inhibition de Ia reproduction. Les plantes les plus actives appartiennent a Ia famille des Labiees.Apres extraction des huiles essentielle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…However, with the new technologies currently available it is possible to increase their residual efficacy. The active products can be encapsulated, used with polymer resins or synergised by other compound like vanillin [27, 30]. However, this rapid decrease of efficacy cannot explain the lack of efficiency of the compound in tunnel tests.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the new technologies currently available it is possible to increase their residual efficacy. The active products can be encapsulated, used with polymer resins or synergised by other compound like vanillin [27, 30]. However, this rapid decrease of efficacy cannot explain the lack of efficiency of the compound in tunnel tests.…”
Section: Discussionmentioning
confidence: 99%
“…The insecticidal effects of the three plants studied were due to their aromatic odors. Indeed, ethnobotanical observations have shown that there is a traditional practice in the south-west of France for the protection of leguminous seeds by odorous plants (Regnault-Roger and Hamraoui, 2013). The effectiveness of this method was evaluated in the laboratory.…”
Section: Evaluation Of the Germination Rate Of The Stored Seeds Aftermentioning
confidence: 99%
“…The effectiveness of this method was evaluated in the laboratory. The insecticidal activity of aromatic plants is exerted on two levels: a lethal effect on adult populations and an inhibition of reproduction (Regnault-Roger and Hamraoui, 2013). According to the same authors, aromatic plants harbor within them a true molecular arsenal of insecticidal or insect repellent substances capable of inducing plant protection.…”
Section: Evaluation Of the Germination Rate Of The Stored Seeds Aftermentioning
confidence: 99%
“…). Also, the chickpea weevil Callosobruchus maculatus may infest the plant Cicer arietinum in fields and stocks; in addition, it infects other leguminous nonhost plants which have an economic importance in developing countries as cowpea ( Vigna unguiculata ) and sap ( Vicia faba ) (Regnault and Hamraoui ).…”
Section: Introductionmentioning
confidence: 99%